Asuransi Usaha Tani Padi Syariah berbasis Indeks Curah Hujan - Agung Prabowo; Diah Paramita Amitarwati (Jurnal Dinamika Ekonomi Pembangunan, 2025)
Since 2016, the Government of the Republic of Indonesia has implemented the Rice Farming Insurance (AUTP) program as mandated by law. In the context of Central Java, with its large Muslim population and successful implementation of sharia economics, it is necessary to develop an AUTP model based on sharia principles. This research aims to create an AUTP model by applying sharia principles (Sharia AUTP or AUTPS) based on a rainfall index and to determine the amount of contribution and compensation within the AUTPS framework. The research methodology employs literature study and model development through stages of planning, analysis, pre-design, actuarial calculation, and final design. The research data comprises rainfall and rice production data from Brebes Regency for the years 2018–2022. The novelty of this research lies in the application of sharia principles and the use of a rainfall index to replace crop failure-based insurance. Consequently, the actuarial calculation for implementing contributions and compensation is based on the rainfall index. The contribution amount is calculated using the Black-Scholes Cash-or-Nothing Put Option equation, while compensation is calculated using the historical burn analysis method. The research results in a proposed rainfall index-based AUTPS model, where the contribution amount is determined based on rainfall percentiles, and compensation payments are categorized as maximum compensation, partial compensation, or no compensation. The mechanism for managing contributions (premiums) follows sharia principles and yields two types of AUTPS: AUTPS-R (without a savings element) and AUTPS-RI (with a savings element). The recommendation from this research is the need to pilot the developed concept in collaboration with a sharia insurance company before it is adopted as a policy by the Regional Government of Central Java Province.